PENGGUNAAN METODE KESEBANGUNAN UNTUK MENINGKATKAN KEMAMPUAN PENERAPAN KONSEP FISIKA SISWA KELAS VIII SMP PGRI 396 KELAPA DUA PADA MATERI CAHAYA - Nomeni, Rosiana; Arif, Muhammad (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Research by similarity method has been carried out in order to determine the application of the concept of capacity building physics of light material , a class VIII student at SMP PGRI 396 Kelapa Dua . This research is a form of pre- experimental study with a one group pretest posttest design . The sample consists of one class is class VIII - 2 which totaled 36 students . The research instrument used was a test application of the concept . Based on the analysis of data using the t test showed significant PSPP 0.00. It can be concluded that there is an increased ability of the application of the concept of light material with similarity method for class VIII SMP PGRI 396 Kelapa Dua. Keywords: The applicability of the concepts, and methods of similarity.